Frequency of borderline personality disorder in patients with polycystic ovary syndrome and its relation with aggression - Baykara, Sema; Yakar, Burkay; Kilinc, Faruk; Korkmaz, Sevda; Atmaca, Murad (Cukurova Univ, Fac Medicine, 2020)
Purpose: The aim of this study was to investigate the incidence of borderline personality disorder (BPD) and its relationship with aggression in patients with polycystic ovary syndrome (PCOS). Materials and Methods: Eightyeight patients diagnosed with PCOS and met the study criteria were included in the study. The patients were interviewed by the psychiatrist after the endocrinological evaluations. Structured Clinical Interview for DSM (Diagnostic and Statistical Manual of Mental Disorders)-IV/Clinical Version (SCID-I/CV), sociodemographic data form, Borderline Personality Inventory (BPI), Buss-Perry Aggression Questionnaire (BPAQ) were applied. Results: The mean age of the patients was 22.39 +/- 3.41. 27.3% (n = 24) of patients was diagnosed with BPD. BPAQ sub scale scores and BPAQ total scores increased as BPI score increased in all PCOS patients. Verbal aggression, anger subscales scores, and total BPAQ score increased as the BPI score increased in PCOS patients with BPD. Conclusion: The results of the study show that PCOS is accompanied by high rates of comorbid BPD. The consistence of both diagnoses together resulted in significantly higher aggression scores than PCOS alone. Adding psychopharmacological and psychotherapeutic approaches to the treatment of PCOS patients, which may be effective in the treatment of BPD, may increase the success of the treatment.
Keywords: Polycystic ovary syndrome; borderline personality disorder; aggression